A RARE CASE OF BILATERAL FLEXOR CARPI ULNARIS VARIATION: ANATOMICAL AND CLINICAL CONSIDERATIONS AND LITERATURE REVIEW. Un caso raro de variación bilateral del músculo flexor carpi ulnaris-significado anatómico y clínico y revisión literaria - Alexandar Iliev; Georgi P. Georgiev; Boycho Landzhov (Asociación Argentina de Anatomía Clínica, 2016)
Various aberrant muscles and fibro-tendinous structures have been identified in the anterior wrist, some of them blamed to be possible causes for neurovascular compression syndromes. Herewith, we describe such an intriguing structure related to the flexor carpi ulnaris muscle. During routine dissection of both upper limbs of an adult cadaver, an interesting crescent-shaped fibro-tendinous structure was identified bilaterally, arising broadly from the lateral side of the distal tendon of the flexor carpi ulnaris. This aberrant structure arched over the ulnar artery and nerve before they enter the canal of Guyon and the median nerve just before the carpal tunnel. Further distally, the fibro-tendinous arch narrowed and interlaced with the flexor retinaculum and palmar aponeurosis longitudinal fibres. In this case there was also concomitant bilateral absence of the palmaris longus muscle. Because this aberrant fibro-tendinous arch has very close relations to the median nerve and ulnar nerve and artery in the wrist, it may possibly cause neurovascular compression during some muscle activity. Varios músculos y estructuras fibro-tendinosas aberrantes se han identificado en la parte anterior de la muñeca, muchas de las cuales se considera que pueden causar síndromes de compresión neurovascular. A continuación describimos una tal estructura relacionada con el músculo flexor carpi ulnaris. Durante disecciones de rutina de ambos miembros superiores de cadáveres de adultos fue descubierta una estructura fibro-tendinosa con forma de medialuna en ambos miembros originando de la parte lateral del tendón distal del flexor carpi ulnaris. Esta estructura formaba un arco pasando sobre y cubriendo la arteria y el nervio ulnar antes de que entren en el canal de Guyon, y sobre el nervio mediano justo antes de que entre en el canal carpal. Este arco fibro-tendinoso seguía estrechándose hasta entrelazarse con el ligamento transverso del carpo y las fibras longitudinales de la aponeuorisis palmar .En este mismo caso el músculo palmaris longus estaba ausente en ambas manos. Esta conexión entre el arco fibro-tendinoso y el nervio mediano, la arteria y el nervio ulnar en la muñeca posiblemente puede causar compresión neurovascular durante cierta actividad muscular.